Labrador odyssey : the journal and photographs of Eliot Curwen on the second voyage of Wilfred Grenfell, 1893 - Curwen, Eliot (McGill-Queen's/Hannah Institute studies in the history of medicine, health, and society, 1996)
"A religious, well-educated Victorian, Eliot Curwen takes us into the heart of the colonial society he encountered. His journal provides insights into its pervasive sectarianism, the tawdry political world of St John's, the rudimentary conditions aboard the fishing schooners, and the poverty of the Labrador "livyers," the permanent white settlers who had intermarried with the Inuit. He provides fresh details about the lives of the Moravian Brethren, the first missionaries to the Native population, and comments on the wildlife, the natural environment, and the general disposition of the countryside. Curwen's candid remarks about Grenfell reveal details about the young missionary and social reformer not found elsewhere. The introduction and annotations by Ronald Rompkey, Grenfell's biographer, establish the historical, political, and social contexts of the journal. Rompkey has included official letters and reports from Grenfell and other members of the expedition to supplement Curwen's rather private account, as well as numerous photographs taken by both Curwen and Grenfell to publicize their work."--Jacket.